Alarm Reminder Pada Kelas Ibu Hamil Masyarakat Desa Kepuharjo Kecamatan Cangkringan - Galuh Tunggal Prastiti; Nurmawati Nurmawi Aman; Dana Daniati; Deasy elvianita; Dea Lestari; Maria Stefania (J.Abdimas: Community Health, 2020)
Indicators of success in the ability of a country's health services are determined by the high and low maternal mortality rate (MMR) and infant mortality rate (IMR). One of the government policies that have been implemented as a realization of the MDG's goals to reduce child mortality and improve maternal health and also as an effort to bring public health services closer is through the pregnant women class program. The innovation "Alarm Reminder" as a reminder of the level of awareness of mothers during visits to the class program for pregnant women at Pustu, Kepuharjo Village, Cangkringan District, Sleman Regency DIY.